First Person and Third Person Perspective in Virtual Reality: Analysis of Cybersickness Symptoms - I Gde Agung Sri Sidhimantra; Darlis Herumurti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
Advances in technology makes it easier to gain access to the virtual world. This has led to more and more application and games being targeted towards the virtual world. But with the growing popularity of the virtual world, cybersickness has grown in popularity as well. This study aims to evaluate the factors affecting cybersickness in the Virtual Reality (VR) environment. There are few factors causing the effect of cybersickness in VR like duration, field of view, speed, habituation, and susceptibility of said user. Those factors affect differently in first person perspective(1pp) and third person perspective(3pp). To measure the cybersickness, a Virtual Reality Questionnaire (VRSQ) measurement index is utilized. The experiment was conducted with the following settings. The participants consisted of 20 males and 4 females who never used VR before. They performed task using short games. It consisted in total of 4 tasks (2 types of game (action and adventure) x 2 perspective (1pp and 3pp) = 4 tasks). The Latin Square design was used to minimize the effect of order. Then, a questionnaire was conducted after each treatment. Paired Dependent T-Tests was performed to check if there are differences in oculomotor, disorientation and VRSQ total score. There was a significant difference in 1pp and 3pp in both games. It is recommended to use third person perspective to reduce the cybersickness in VR environment.